Research on NFV fault association and fault self-healing - Binhong MAO; Zhiming YANG (Dianxin kexue)
NFV implements the hardware and software decoupling of telecommunications network equipment,gets rid of the dependence on dedicated hardware equipment.NFV brings benefits such as resource sharing,automatic deployment,flexibility and other features,but it also brings some problems such as more fault points,difficult fault analysis and so on.It results in NFV network operation and maintenance more difficult.The NFV fault process and fault association were analyzed,and guidance for fault location processing in NFV was provided.At the same time,the VNF fault self-healing implementation scheme was given to realize the network element and service fault self-healing,and improve capability of automatic operation and maintenance.